n-Hexane Fraction of Cucumis melo L. Cultivar Gama Melon Parfum: An in vitro Study in MCF7 and T47D Cells Line - Salamah, Rohmi; Wijayanti, Nastiti; Widiyanto, Slamet (Cell and BioPharmaceutical Institute, 2025)
Background: Cucumis melo a melon species, typically has a sweet taste. Some cultivars are known for their distinctive bitter flesh due to its higher levels of cucurbitacin. Cucurbitacin is semipolar compound that has anticancer properties. However, the anticancer effects of cucurbitacin from gama melon parfum (GMP) have not been widely studied. The use of n-Hexane as a non-polar solvent in GMP melon fractionation is to dissolve the non-polar parts of the plant. However, Cucurbitacin was found in the n-hexane fraction of Cucurbita pepo L. Therefore, this study will investigate the presence of Cucurbitacin in the n-Hexane fraction and its effects on breast cancer cells T47D and MCF7.Materials and methods: Dry simplicia of GMP melon fruit were macerated using methanol and fractionated using n-hexane. The presence of cucurbitacin was detected using the high-performance liquid chromatography (HPLC) method. Cell cytotoxicity tests were assessed using the MTT assay, with concentrations of 7.8125, 15.625, 31.25, 62.5, and 125 µg/mLResults: Cucurbitacin compounds were detected in the n-hexane fraction at a concentration of 7.6 µg/mL per 10 mg of n-hexane fraction. MCF7 cell viability was lower than that of T47D cells across all concentrations tested. MCF7 cell viability was below 50% at a concentration of 62.5 µg/mL. In contrast, T47D cell viability remained at 100% even at the highest concentration of 125 µg/mL. The IC50 value of MCF7 cells was 43.5 µg/mL.Conclusion: The cucurbitacin content in the n-Hexane fraction was 7.6 µg/mL per 10mg fraction. At this concentration, it moderately inhibits the proliferation of MCF7 cells.Keywords: gama melon parfum, cucurbitacin, HPLC, T47D, MCF7